An Unusual Presentation of Idiopathic Multicentric Castleman Disease: The Great Masquerader - Mazumder, Sujaya; Naidu, Raji Tejas; Cherian, Susan; Mayura, Sruthi; Chaturvedi, Uma Pankaj (Annals of Pathology and Laboratory Medicine, 2020)
Castleman disease is an uncommon, non-clonal, lymphoproliferative disorder characterized by lymphadenopathy and symptoms related to hypercytokinemia. Clinically it is classified as unicentric and multicentric disease. Multicentric disease is further subclassified as HHV- 8 associated disease and idiopathic disease, which is the rarest subtype. The incidence of idiopathic disease is estimated to be 5 per million person years. The diagnosis of Idiopathic Multicentric Castleman disease is complicated by an array of clinical mimics and non-specific symptoms. We report a rare case of Idiopathic Multicentric Castleman disease in a young female where a detailed pathological work up helped to secure the diagnosis and exclude its mimics.